Building classroom discipline - Charles, C. M. 4 0 16; Senter, Gail W.; 5 (Boston : Pearson/Allyn and Bacon, 2008)
Offers teachers practical advice to help them develop personal systems of discipline that match their individual philosophies and personalities and meet the needs of their students, schools, and communities.
Includes bibliographical references and index.
Professional.
Keywords: 2 -- 0; 6; School discipline.;Classroom management. -- 20; 20; 2